Comparison of Children with Migraine and Those with Tension-Type Headache for Psychiatric Symptoms and Quality of Life - Açıkel, Burak Sadettin; Bilgiç, Ayhan; Derin, Hatice; Eroğlu, Arzu; Akça, Ömer Faruk; Çaksen, Hüseyin (Journal of Pediatric Neurology, 2019)
This study compared the severity of depression, anxiety, somatization, anxiety sensitivity, sleep disturbances, and quality of life (QoL) among children with migraine, children with tension-type headache (TTH), and healthy children. A total of 37 children with migraine, 22 with TTH, and a healthy control group (n = 35) participated in this study. Children with migraine exhibited higher depression and somatization and lower QoL scores than those in the control group. General sleep disturbances, bedtime resistance, sleep onset delay, sleep duration, sleep anxiety, night wakings, sleep-disordered breathing, and daytime sleepiness scores were also higher in those in the migraine group than in the control group. Regression models indicated that the severity of headache and depression scores significantly affected the QoLs of children with headache disorder as a whole. Migraine is associated with depression, somatization, sleep disturbances, and poor QoL, whereas TTH is associated with only sleep disturbances in childhood. The impact of headache on the QoL occurs mainly through the headache-specific and psychiatric factors.
Keywords: children; headache; migraine; tension-type headache; quality of life